A low-temperature high-power ternary positive electrode material and preparation method thereof
By adding magnesium chromate and lithium titanium zirconium phosphate to the ternary positive electrode material of lithium-ion batteries, and covering aluminum fluoride and boron oxide layers on the surface of the material, the problem of degradation of lithium-ion batteries under low temperature conditions is solved, and the performance of lithium-ion batteries is improved. The battery's low temperature performance and cycle life are reduced and the cost is reduced.
Patent Information
- Application Number
- CN202210721702.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-06-24
AI Technical Summary
The performance of lithium-ion batteries is affected under low temperature conditions, especially when the temperature in northern China is low in winter, which affects the battery's service life.
Using a preparation method of a ternary positive electrode material, by adding magnesium chromate and lithium titanium zirconium phosphate during the sintering process, the crystal spacing and melting point of the material are changed, the particle size and internal resistance are reduced, and the surface of the material is coated with fluorination. Aluminum and boron oxide layers improve ionic conductivity and cycling performance.
It improves the low-temperature performance and rate performance of the material, extends the cycle life of the battery, and reduces the processing cost and the corrosion of the material by the electrolyte, making it suitable for industrial production.
Smart Images

Figure CN115000377B_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a low-temperature high-power ternary positive electrode material and a preparation method thereof, belonging to the technical field of lithium ion batteries. Background Art
[0002] New energy vehicles are a national strategic emerging industry. With the continuous upgrading of automotive power batteries, lithium-ion batteries have received widespread attention as energy storage due to their advantages such as high specific capacity, long cycle life and good safety performance.
[0003] NCM ternary cathode material has the advantages of high capacity, long life, low cost and abundant raw material sources, and is a lithium-ion battery material with great application prospects. With the expansion of lithium battery application fields, the disadvantages of low temperature performance are becoming more and more obvious. The winter temperature in northern my country is generally around minus 30℃. During the charging and discharging process, the performance of lithium-ion batteries is greatly affected by the environment, especially under low temperature conditions, which affects the battery life. Summary of the invention
[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a low-temperature high-power ternary positive electrode material and a preparation method thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a ternary positive electrode material comprises the following steps:
[0007] (1) Putting the ternary precursor, lithium salt, magnesium chromate, and lithium zirconium titanium phosphate into a mixing tank and mixing them evenly by dry method until there are no white spots to obtain a mixed material; preferably, the molecular formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, wherein 0<x<1, 0<y<1; the lithium salt is lithium nitrate, lithium carbonate or lithium hydroxide; the molar ratio of the ternary precursor and the lithium salt is 1:(1.01-1.08); the mass of magnesium chromate in the mixture is 0.3-1.2wt% of the mass of the ternary precursor; the mass of lithium zirconium titanium phosphate in the mixture is 0.5-1.5wt% of the mass of the ternary precursor.
[0008] (2) placing the obtained mixed material into a sagger and sintering it in an oxygen or air atmosphere to obtain a sintered material; the sintered material is crushed in a pulverizer, sieved through a 400-mesh sieve to obtain particles with uniform particle size distribution, and the crushed material is obtained after demagnetization; preferably, the sintering process is as follows: first, heating the temperature to 300°C-600°C at a heating rate of 1-3°C / min, and keeping the temperature for 3-5h; then, heating the temperature to 750°C-960°C at a heating rate of 3-5°C / min, and keeping the temperature for 8-15h.
[0009] (3) First, aluminum fluoride and crushed material are uniformly mixed in a mass ratio of (0.004-0.02): 1, and kept in a muffle furnace at 300℃-650℃ for 6-8h, and then crushed to obtain a material coated with an aluminum fluoride layer; aluminum fluoride can be uniformly coated on the surface of the material, blocking the positive electrode material from contacting the electrolyte during the battery charging and discharging process, reducing the occurrence of side reactions on the surface of the material, and improving the cycle performance of the material. Then, boron oxide is mixed with the material coated with the aluminum fluoride layer, and kept in a temperature of 300℃-650℃ for 6-8h, and a boron oxide layer is formed on the outer layer of the material, and then crushed to obtain the target product. Boron oxide is more likely to absorb moisture in the air to generate boric acid, thereby reducing the water absorption of lithium oxide on the surface of the material to convert into lithium hydroxide and lithium carbonate, thereby achieving the effect of reducing the residual alkali on the surface of the material, and the generated boric acid can further acidify the surface of the material, reduce the corrosion of the electrolyte on the surface of the material, and further improve the cycle performance of the material.
[0010] The present invention also provides a ternary positive electrode material prepared by the above-mentioned preparation method.
[0011] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0012] (1) The present invention adds magnesium chromate and lithium titanium zirconium phosphate to the starting raw materials. During the sintering process, magnesium chromate replaces nickel and cobalt elements through bulk phase doping, changes the crystal spacing of the material, can reduce the particle size, increase the specific surface area of the material, and thus improve the low-temperature performance of the material; lithium titanium zirconium phosphate doping reduces the degree of lithium-nickel mixing, reduces the generation of irreversible phase change during the charge and discharge process, improves the ion conductivity, and reduces the internal resistance of the material, so as to improve the rate performance of the material. The present invention adds magnesium chromate and lithium titanium zirconium phosphate. These two substances are added to the sintering at the same time. Each material has a different melting point, which is equivalent to the role of a solvent. The melting point of the material reaction can be reduced, the temperature of the crystal reaction can be reduced, and the processing cost can be reduced. In addition, zirconium ion doping in lithium titanium zirconium phosphate can stabilize the crystal structure, and titanium ion doping can effectively expand the lithium ion migration channel and improve the migration efficiency. The battery has a higher ion conductivity under low temperature (<-20°C) conditions, and the battery has a higher capacity retention rate and excellent rate performance during a long cycle.
[0013] (2) Boron oxide and aluminum fluoride double-layer coating is used. The aluminum fluoride coating layer blocks contact with the electrolyte during the battery charging and discharging process, reduces the occurrence of side reactions on the material surface, and improves the material's cycle performance. Boron oxide is more likely to absorb moisture in the air to generate boric acid, thereby reducing the absorption of water by lithium oxide on the material surface and converting it into lithium hydroxide and lithium carbonate, thereby achieving the effect of reducing the residual alkali on the material surface. The generated boric acid can further acidify the material surface, reduce the corrosion of the electrolyte on the material surface, and further improve the material's cycle performance.
[0014] (3) The method of the present invention has simple preparation process and low energy consumption, and is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a 3000x SEM photograph of the crushed material obtained in step (2) of this Example 1.
[0016] Figure 2 This is a 3000x SEM photograph of the final material obtained in step (3) of Example 1 of the present invention. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0018] Example 1
[0019] (1) Take Ni 0.5 Co 0.2 Mn 0.3 (OH)2 is the ternary precursor, lithium nitrate is the lithium salt, and Ni is weighed in a molar ratio of 1:1.05. 0.5 Co 0.2 Mn 0.3 (OH)2 and lithium nitrate; based on the mass of the ternary precursor, 1wt% magnesium chromate and 0.7wt% lithium zirconium titanium phosphate were added respectively; the above raw materials were put into a ball mill and mixed for 40 minutes to obtain the required mixed material;
[0020] (2) The obtained mixed material is placed in a sagger and sintered in a muffle furnace under air atmosphere. The sintering temperature is gradient sintering: the temperature is raised from room temperature to 550°C, the sintering time is 3h, and the heating rate is 1.5°C / min; then the temperature is raised to 910°C, the sintering time is 8h, and the heating rate is 3°C / min. The heating rate is relatively slow in the front, so the crystals can have sufficient time to form and grow. The heating rate is reduced and the sintering temperature is moderate in the back to prevent the crystals from growing excessively. After sintering, the sintered material is crushed in a universal crusher for 30s and sieved through a 400-mesh sieve to obtain a crushed material.
[0021] (3) Layering aluminum fluoride layers and boron oxide layers on the outer surface of the pulverized material, the method is as follows: aluminum fluoride and the pulverized material are uniformly mixed together at a mass ratio of 0.015:1, and then placed in a muffle furnace for sintering at 650°C for 8 hours. After the sintering is completed, the material is crushed in a universal crusher for 30 seconds, and sieved through a 400-mesh sieve to obtain a material coated with an aluminum fluoride layer; boron oxide and the material coated with an aluminum fluoride layer are uniformly mixed together at a mass ratio of 0.015:1, and then placed in a muffle furnace for sintering at 650°C for 8 hours. After the sintering is completed, the material is placed in a universal crusher for pulverizing for 30 seconds, and screened through a 400-mesh sieve to obtain a final product.
[0022] The materials obtained in step (2) and step (3) of Example 1 were subjected to SEM examination, and the results were as follows: Figure 1 and Figure 2 As shown in the figure, it can be seen that the primary particle size of the sintered material particles is small, the crystal structure is relatively complete and has no defects, the crystal structure is optimized, and a layer of coating is attached to the surface of the coated material to prevent the erosion of the electrolyte, improve the material cycle performance and capacity retention rate.
[0023] Example 2
[0024] (1) Take Ni 0.6 Co 0.1 Mn 0.3 (OH)2 is the ternary precursor, lithium nitrate is the lithium salt, and Ni is weighed in a molar ratio of 1:1.05. 0.6 Co 0.1 Mn 0.3 (OH)2 and lithium nitrate; based on the mass of the ternary precursor, 1wt% magnesium chromate and 0.7wt% lithium zirconium titanium phosphate are added respectively; the above raw materials are put into a mixing tank and mixed evenly by dry method without white spots to obtain the required mixed material;
[0025] (2) The obtained mixed material is placed in a sagger and sintered in an air atmosphere. The sintering temperature is a gradient sintering: the temperature is raised from room temperature to 600°C, kept for 3 hours, and the heating rate is 1.5°C / min; then the temperature is raised to 910°C and kept for 8 hours, and the heating rate is 3°C / min. After the sintering is completed, the sintered material is crushed in a crusher and sieved through a 400-mesh screen to obtain a crushed material.
[0026] (3) Layering aluminum fluoride layers and boron oxide layers on the outer surface of the pulverized material, the method is as follows: aluminum fluoride and the pulverized material are uniformly mixed together at a mass ratio of 0.015:1, and then placed in a muffle furnace for sintering at 650°C for 8 hours. After the sintering is completed, the material is crushed in a universal crusher for 30 seconds, and sieved through a 400-mesh sieve to obtain a material coated with an aluminum fluoride layer; boron oxide and the material coated with an aluminum fluoride layer are uniformly mixed together at a mass ratio of 0.015:1, and then placed in a muffle furnace for sintering at 650°C for 8 hours. After the sintering is completed, the material is placed in a universal crusher for pulverizing for 30 seconds, and screened through a 400-mesh sieve to obtain a final product.
[0027] Example 3
[0028] (1) Take Ni 0.6 Co 0.1 Mn 0.3 (OH)2 is the ternary precursor, lithium nitrate is the lithium salt, and Ni is weighed in a molar ratio of 1:1.01. 0.6 Co 0.1 Mn 0.3 (OH)2 and lithium nitrate; based on the mass of the ternary precursor, add 0.3wt% magnesium chromate and 0.5wt% lithium zirconium titanium phosphate respectively; put the above raw materials into a mixing tank and mix them evenly by dry method without white spots to obtain the required mixed material;
[0029] (2) The obtained mixed material is placed in a sagger and sintered in an air atmosphere. The sintering temperature is a gradient sintering: the temperature is raised from room temperature to 600°C, kept at this temperature for 4 hours, and the heating rate is 1.5°C / min; then the temperature is raised to 910°C and kept at this temperature for 15 hours, and the heating rate is 3°C / min. After the sintering is completed, the sintered material is crushed in a crusher and sieved through a 400-mesh screen to obtain a crushed material.
[0030] (3) Layering aluminum fluoride layers and boron oxide layers on the outer surface of the pulverized material, the method is as follows: aluminum fluoride and the pulverized material are uniformly mixed together at a mass ratio of 0.004:1, and then placed in a muffle furnace for sintering at 300°C for 6 hours. After the sintering is completed, the material is crushed in a universal grinder for 30 seconds, and sieved through a 400-mesh sieve to obtain a material coated with an aluminum fluoride layer; boron oxide and the material coated with an aluminum fluoride layer are uniformly mixed together at a mass ratio of 0.004:1, and then placed in a muffle furnace for sintering at 300°C for 60 hours. After the sintering is completed, the material is placed in a universal grinder for crushing for 30 seconds, and screened through a 400-mesh sieve to obtain a final product.
[0031] Example 4
[0032] (1) Take Ni 0.6 Co 0.1 Mn 0.3(OH)2 is the ternary precursor, lithium nitrate is the lithium salt, and Ni is weighed in a molar ratio of 1:1.08. 0.6 Co 0.1 Mn 0.3 (OH)2 and lithium nitrate; based on the mass of the ternary precursor, 1.2wt% magnesium chromate and 1.5wt% lithium zirconium titanium phosphate were added respectively, and the above raw materials were put into a mixing tank and mixed evenly by dry method without white spots to obtain the required mixed material;
[0033] (2) The obtained mixed material is placed in a sagger and sintered in an air atmosphere. The sintering temperature is a gradient sintering: the temperature is raised from room temperature to 600°C, kept at this temperature for 3 hours, and the heating rate is 1.5°C / min; then the temperature is raised to 910°C and kept at this temperature for 10 hours, and the heating rate is 3°C / min. After the sintering is completed, the sintered material is crushed in a crusher and sieved through a 400-mesh screen to obtain a crushed material.
[0034] (3) Layering aluminum fluoride layers and boron oxide layers on the outer surface of the pulverized material, the method is as follows: aluminum fluoride and the pulverized material are uniformly mixed together at a mass ratio of 0.02:1, and then placed in a muffle furnace for sintering at 500°C for 8 hours. After the sintering is completed, the material is crushed in a universal grinder for 30 seconds, and sieved through a 400-mesh sieve to obtain a material coated with an aluminum fluoride layer; boron oxide and the material coated with an aluminum fluoride layer are uniformly mixed together at a mass ratio of 0.02:1, and then placed in a muffle furnace for sintering at 500°C for 8 hours. After the sintering is completed, the material is placed in a universal grinder for crushing for 30 seconds, and screened through a 400-mesh sieve to obtain the final product.
[0035] Comparative Example 1
[0036] The difference between this comparative example and Example 1 is that magnesium chromate and lithium zirconium titanium phosphate are not added in step (1), and the other steps are the same as those in Example 1.
[0037] Comparative Example 2
[0038] The difference between this comparative example and Example 1 is that no aluminum fluoride and boron oxide coating is performed, that is, step (3) is not performed, and the other steps are the same as those in Example 1.
[0039] Comparative Example 3
[0040] The difference between this comparative example and Example 1 is that magnesium chromate is not added in step (1), and the other steps are the same as those in Example 1.
[0041] Comparative Example 4
[0042] The difference between this comparative example and Example 1 is that lithium zirconium titanium phosphate is not added in step (1), and the other steps are the same as Example 1.
[0043] Comparative Example 5
[0044] The difference between this comparative example and Example 1 is that aluminum fluoride coating is not performed in step (3), and the other steps are the same as Example 1.
[0045] Comparative Example 6
[0046] The difference between this comparative example and Example 1 is that boron oxide coating is not performed in step (3), and the other steps are the same as Example 1.
[0047] The materials prepared in the above-mentioned embodiments and comparative examples were characterized and tested for performance. The test results are shown in Table 1.
[0048] Table 1 Physical properties analysis results of products prepared in various examples and comparative examples
[0049]
[0050]
[0051] The products prepared in the embodiments and comparative examples were used as positive electrode active materials, and graphite was used as the negative electrode to assemble soft-pack batteries. The battery performance tester was used to test the battery performance. The charge and discharge cut-off voltage was 3 to 4.35 V, and the charge and discharge cycle was 1C. The results are shown in Table 2.
[0052] Table 2 Electrical performance test results of batteries composed of products prepared in various embodiments and comparative examples
[0053]
[0054] Combining Table 1 and Table 2, it can be seen that the addition of magnesium chromate and lithium titanium zirconium phosphate additives significantly reduces the particle size of the material and increases the specific surface area. The larger specific surface area can increase the contact area between the electrolyte and the material, reduce the lithium ion migration path, and thus improve the low temperature and rate performance of the material. The aluminum fluoride and boron oxide coating layers significantly improve the cycle performance of the material, and the cycle performance is best when aluminum fluoride and boron oxide are double-coated. The material doped with magnesium chromate and lithium titanium zirconium phosphate and double-coated with aluminum fluoride and boron oxide has the best comprehensive performance.
[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a ternary positive electrode material, characterized in that: The following steps are involved: (1) uniformly mixing a ternary precursor, a lithium salt, magnesium chromate, and lithium titanium zirconium phosphate to obtain a mixed material; the mass of magnesium chromate in the mixed material is 0.3-1.2wt% of the mass of the ternary precursor; the mass of lithium titanium zirconium phosphate in the mixed material is 0.5-1.5wt% of the mass of the ternary precursor; (2) sintering the mixed material in an oxygen-containing atmosphere, and crushing the sample after sintering to obtain a crushed material; (3) mixing the crushed material with aluminum fluoride, keeping the mixture at a temperature of 300°C-650°C for 6-8 hours, and crushing the mixture to obtain a material coated with an aluminum fluoride layer; mixing boron oxide with the material coated with an aluminum fluoride layer, keeping the mixture at a temperature of 300°C-650°C for 6-8 hours, and crushing the mixture to obtain a target product; In step (3), the mass ratio of the aluminum fluoride to the crushed material is (0.004-0.02):1; the mass ratio of the boron oxide to the crushed material is (0.004-0.02):
1.
2. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: In step (1), the molecular formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, wherein 0<x<1, 0<y<1.
3. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: In step (1), the lithium salt is lithium nitrate or lithium carbonate.
4. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: In step (1), the molar ratio of the ternary precursor to the lithium salt is 1:(1.01-1.08).
5. The method for preparing the ternary cathode material according to claim 1, characterized in that: In step (2), the oxygen-containing atmosphere is an oxygen or air atmosphere.
6. The method for preparing a ternary cathode material according to claim 1, characterized in that: In step (2), the sintering process is: firstly, heating to 300-600°C at a heating rate of 1-3°C / min, and keeping warm for 3-5h; then, heating to 750-960°C at a heating rate of 3-5°C / min, and keeping warm for 8-15h.
7. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method for modifying lithium-rich manganese-based cathode material
CN104681809A
High-nickel ternary positive electrode composite material and preparation method thereof
CN108417797A
Method for preparing high-nickel ternary material under assistance of fluxing agent, obtained product and application
CN111606362A
Coated ternary positive electrode material, preparation method thereof and lithium ion battery
CN112993259A
Precursor of positive electrode active material for nonaqueous electrolyte secondary batteries and manufacturing method thereof, and positive electrode active material for nonaqueous electrolyte secondary batteries and manufacturing method thereof
JP2015191848A
